Enhancing Medicine Access with E-Pharmacy using MERN Stack - P., Abinaya S; P., Dharshan; S., Abinesh (Journal of Trends in Computer Science and Smart Technology, 2024)
The worldwide pandemic in 2019 has led major companies to shift from offline to online platforms. This shift has served as a major reason to promote the significance of e-pharmacy in revolutionizing the supply of medicines to consumers worldwide. However, the lack of specific regulatory frameworks has affected the overall market growth of e-pharmacy, causing delays or failures in medicine transactions. The proposed method aims to streamline the transaction process between the consumer and the supplier using verification techniques. The user interface, developed using MERN technology, enhances the availability of medicine, especially for severe diseases like cancer. Furthermore, the research also seeks to reduce the cost of medicine by utilizing government health insurance with additional verification steps to ensure timely, free medicines for those in need. Integrating e-pharmacy with government health insurance policies and verification techniques aims to improve the platform, offering better and free medicine delivery for patients in need.